Investigation of the corrosion behaviour of AA 2024-T3 in low concentrated chloride media - Queiroz, F. M.; Magnani, M. [UNESP]; Costa, I.; de Melo, H. G. (Pergamon-Elsevier B.V. Ltd, 2008)
Aluminium alloy (AA) 2024-T3 is an important engineering material due to its widespread use in the aerospace industry. However, it is very prone to localized corrosion attack in chloride containing media, which has been mainly associated to the presence of coarse intermetallics (IMs) in its microstructure. In this work the corrosion behaviour of AA 2024-T3 in low concentrated chloride media was investigated using microscopy and electrochemical methods. TEM/EDS observations on non-corroded samples evidenced the heterogeneous composition within the IMs. In addition, SEM observations showed that intermetallics with the same nominal composition present different reactivity, and that both types of coarse IMs normally found in the alloy microstructure are prone to corrosion. Moreover, EDS analyses showed important compositional changes in corroded IMs, evidencing a selective dissolution of their more active constituents, and the onset of an intense oxygen peak, irrespective to the IM nature, indicating the formation of corrosion products. on the other hand, the results of the electrochemical investigations, in accordance with the SEM/EDS observations, evidenced that IMs corrosion dominates the electrochemical response of the alloy during the first hours of immersion in the test electrolyte. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Aluminium; Intermetallics; EIS; SEM; TEM